1991
DOI: 10.1105/tpc.3.9.923
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal expression of a maize lipid transfer protein gene.

Abstract: We studied the temporal and spatial pattern of lipid transfer protein (LTP) gene expression, as well as the localization of this protein, in maize. Using an LTP gene, we observed an accumulation of LTP mRNA in embryos and endosperms during seed maturation. LTP gene expression was also investigated in young seedlings. After germination, the leve1 of LTP mRNA in the coleoptile increased, with a maximum at 7 days, whereas LTP mRNA levels were low in the scutellum and negligible in roots. The high levels of LTP mR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(48 citation statements)
references
References 16 publications
2
45
1
Order By: Relevance
“…Plant nsLTPs share 43~o to 64~o amino acid sequence homology with each other and have the following common characteristics: (1) the presence of eight cysteine residues at conserved locations; (2) a signal peptide; (3) a molecular mass of ca. 9 kDa; and (4) a basic isoelectric point of approximately 9 [2,17]. These characteristics are also applicable to the PVR3 protein, except that PVR3 protein shows a pI of 6.8.…”
Section: Comparison Of the Pvr3 Protein With Other Plant Proteinsmentioning
confidence: 80%
See 3 more Smart Citations
“…Plant nsLTPs share 43~o to 64~o amino acid sequence homology with each other and have the following common characteristics: (1) the presence of eight cysteine residues at conserved locations; (2) a signal peptide; (3) a molecular mass of ca. 9 kDa; and (4) a basic isoelectric point of approximately 9 [2,17]. These characteristics are also applicable to the PVR3 protein, except that PVR3 protein shows a pI of 6.8.…”
Section: Comparison Of the Pvr3 Protein With Other Plant Proteinsmentioning
confidence: 80%
“…[2,7,14,17,18,23]. On the basis of this result, it was suggested that a ns-LTP isoform might be expressed specifically in root tissue [1,2,17]. The expression pattern of PVR3 cDNA, which is rootspecific (Fig.…”
Section: Modelling Of Pvr3 Proteinmentioning
confidence: 99%
See 2 more Smart Citations
“…Originally it was believed that lipid-binding proteins were possibly involved in lipid transfer between organelles. Three recent observations would strongly question this conclusion: (1) maize lipid transfer protein has been immunolocalized and found predominantly in the external cellular layers and around the leaf veins [128]; (2)the EP2 lipid transfer protein in embryogenic carrot suspensions is secreted into the medium [131]; (3)the Arabidopsis lipid transfer protein has an extracellular location [138]. It is possible that lipid transfer proteins are involved in wax or cutin synthesis.…”
Section: Fatty Acid-binding Proteins/membrane Formation and Targetingmentioning
confidence: 99%